2004
DOI: 10.1111/j.1469-0691.2004.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of Neisseria meningitidis by Greek children: risk factors and strain characteristics

Abstract: Oropharyngeal swabs were cultured from 554 children aged 2-19 years attending nurseries, primary schools and secondary schools in the central Athens area. A questionnaire was completed to identify risk factors for carriage. Susceptibility to antimicrobial agents was determined by Etest. The genetic relatedness of the strains was examined by pulsed-field gel electrophoresis (PFGE), and isolate serogrouping was performed by slide agglutination. Twenty-two (4%) children were carriers of Neisseria meningitidis; se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 20 publications
(24 reference statements)
3
20
1
1
Order By: Relevance
“…The prevalence of Neisseria meningitides in our study was 320(7.8%) from the total population we used it is comparable to the study conducted in Ethiopia by Bårnes GK,et al (10) in Arba Minch, southern Ethiopia 6.6%, in Burkina Faso 7.86% (11), in Turkey by Gazi H. et al 6.2% [1] and study conducted in Greece (7.2%) [12]. In contrary higher prevalence of carriage rate reported in India (10.4%) [13] And lower nasopharyngeal carriage of Neisseria meningitides was reported in healthy Dutch children 46 (1.5%) [12] And in Greece children (4.0%) [14]. our results showed higher nasopharyngeal carriage rate of Neisseria meningitides among older children less than twenty years old.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Neisseria meningitides in our study was 320(7.8%) from the total population we used it is comparable to the study conducted in Ethiopia by Bårnes GK,et al (10) in Arba Minch, southern Ethiopia 6.6%, in Burkina Faso 7.86% (11), in Turkey by Gazi H. et al 6.2% [1] and study conducted in Greece (7.2%) [12]. In contrary higher prevalence of carriage rate reported in India (10.4%) [13] And lower nasopharyngeal carriage of Neisseria meningitides was reported in healthy Dutch children 46 (1.5%) [12] And in Greece children (4.0%) [14]. our results showed higher nasopharyngeal carriage rate of Neisseria meningitides among older children less than twenty years old.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the likely carriage rates in Europe (Dominguez et al , 2001; Pavlopoulou et al , 2004; Bogaert et al , 2005), countries considering a catch‐up campaign will maximize the indirect effects of the programme by including adolescents. These observations are also supported by the findings of mathematical modelling studies (Trotter et al , 2005).…”
Section: Recommendationsmentioning
confidence: 99%
“…Twelve studies involved controlled trials (Gotschlich et al 1969;Artenstein et al 1970;Devine et al 1970;Wenzel et al 1973;Makela et al 1975;Wahdan et al 1977;Greenwood et al 1978;Sivonen 1981;Blakebrough et al 1983;Bjune 1992;Boslego et al 1995;Perkins et al 1998), 10 studies evaluated carriage preand post-vaccination (Bosmans et al 1980;Masterton et al 1988;Dimartino et al 1990;Stroffolini et al 1990;Maiden et al 2002;Fernandez et al 2003;Djibo et al 2004;Eslami-Nejad et al 2005;Caugant et al 2006;Mueller et al 2006) and seven were cross-sectional surveys carried out post-vaccination (Hassan-King et al 1988;Neal et al 1998;Smith et al 1999;Aceitero 2000;Cardenosa et al 2001;Dominguez et al 2001;Pavlopoulou et al 2004).…”
Section: Description Of Studies Reviewedmentioning
confidence: 99%
“…Four studies evaluated a meningococcal serogroup C polysaccharide vaccine (Gotschlich et al 1969;Artenstein et al 1970;Devine et al 1970;Wenzel et al 1973), four studies evaluated a serogroup A polysaccharide vaccine (Gotschlich et al 1969;Makela et al 1975;Wahdan et al 1977;Sivonen 1981), 17 studies a serogroup A + C polysaccharide vaccine (Greenwood et al 1978;Bosmans et al 1980;Blakebrough et al 1983;Hassan-King et al 1988;Masterton et al 1988;Dimartino et al 1990;Stroffolini et al 1990;Neal et al 1998;Smith et al 1999;Aceitero 2000;Cardenosa et al 2001;Dominguez et al 2001;Fernandez et al 2003;Djibo et al 2004;Pavlopoulou et al 2004;Eslami-Nejad et al 2005;Mueller et al 2006) and one study evaluated a tetravalent ACYW135 polysaccharide vaccine (Caugant et al 2006). Only one study has reported on the effect of a meningococcal C conjugate vaccine on carriage (Maiden et al 2002).…”
Section: Description Of Studies Reviewedmentioning
confidence: 99%
See 1 more Smart Citation